2014
DOI: 10.1007/s00436-014-3888-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression of Fasciola gigantica thioredoxin

Abstract: In the present study, a cDNA encoding Trx from F. gigantica (FgTrx) was cloned by polymerase chain reaction (PCR). The sequence of FgTrx, analyzed by BLAST, SignalP, and ClustralW programs, showed 315 bp of an open reading frame (ORF), 12 bp 5'UTR, 78 bp 3'UTR, and the putative FgTrx peptide comprising of 104 amino acids, with a molecular weight of 11.68 kDa, with the active site containing five amino acids (tryptophan, cysteine, glycine, proline, cysteine) with a conserved dithiol motif from the two cysteines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Excretory and secretory products (ESPs), containing many active molecules, have been produced by these parasites under in vitro and in vivo conditions [ 17 ]. Previous reports showed that different molecules of ESPs from F. gigantica (FgESPs) can cause various immune responses—for example, some molecules can simulate host defense against parasites, while other have exerted the opposite effect [ 16 , 18 , 19 , 20 , 21 ]. Of particular importance to their survival is the ability of liver flukes to employ an anti–oxidant, redox-based system that protects the liver flukes against the reactive oxygen and nitrogen species produced by host immune cells and endogenous cellular metabolism [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Excretory and secretory products (ESPs), containing many active molecules, have been produced by these parasites under in vitro and in vivo conditions [ 17 ]. Previous reports showed that different molecules of ESPs from F. gigantica (FgESPs) can cause various immune responses—for example, some molecules can simulate host defense against parasites, while other have exerted the opposite effect [ 16 , 18 , 19 , 20 , 21 ]. Of particular importance to their survival is the ability of liver flukes to employ an anti–oxidant, redox-based system that protects the liver flukes against the reactive oxygen and nitrogen species produced by host immune cells and endogenous cellular metabolism [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike Prx1, however, novel functions of F. hepatica Trx remain to be discovered. Sequence alignments and structural models of the various F. hepatica Trxs with those from other parasites (protozoan and helminth) and mammals reveal a fully conserved structure including the protruding five amino acid motif (WCGPC) at its active site and neighbouring residues vital for its functionality ( Salazar-Calderón et al., 2001 ; Changklungmoa et al., 2014 ). This could infer that FhTrx1 exhibits some or all of the expanding assortment of endogenous and exogenous activities that are emerging for human Trx1 (hTrx).…”
Section: Prx1 and Trx1 – Specialised Immunomodulatory Proteins?mentioning
confidence: 99%